HIV Infection Predisposes to Increased Chances of HBV Infection: Current Understanding of the Mechanisms Favoring HBV Infection at Each Clinical Stage of HIV Infection - Zaongo, Silvere D.; Ouyang, Jing; Chen, Yaling; Jiao, Yan-Mei; Wu, Hao; Chen, Yaokai (Frontiers in Immunology, 2022)
Human immunodeficiency virus (HIV) selectively targets and destroys the infection-fighting CD4+ T-lymphocytes of the human immune system, and has a life cycle that encompasses binding to certain cells, fusion to that cell, reverse transcription of its genome, integration of its genome into the host cell DNA, replication of the HIV genome, assembly of the HIV virion, and budding and subsequent release of free HIV virions. Once a host is infected with HIV, the host’s ability to competently orchestrate effective and efficient immune responses against various microorganisms, such as viral infections, is significantly disrupted. Without modern antiretroviral therapy (ART), HIV is likely to gradually destroy the cellular immune system, and thus the initial HIV infection will inexorably evolve into acquired immunodeficiency syndrome (AIDS). Generally, HIV infection in a patient has an acute phase, a chronic phase, and an AIDS phase. During these three clinical stages, patients are found with relatively specific levels of viral RNA, develop rather distinctive immune conditions, and display unique clinical manifestations. Convergent research evidence has shown that hepatitis B virus (HBV) co-infection, a common cause of chronic liver disease, is fairly common in HIV-infected individuals. HBV invasion of the liver can be facilitated by HIV infection at each clinical stage of the infection due to a number of contributing factors, including having identical transmission routes, immunological suppression, gut microbiota dysbiosis, poor vaccination immune response to hepatitis B immunization, and drug hepatotoxicity. However, there remains a paucity of research investigation which critically describes the influence of the different HIV clinical stages and their consequences which tend to favor HBV entrenchment in the liver. Herein, we review advances in the understanding of the mechanisms favoring HBV infection at each clinical stage of HIV infection, thus paving the way toward development of potential strategies to reduce the prevalence of HBV co-infection in the HIV-infected population.